PENGUJIAN SIFAT FISIK LUMPUR PEMBORAN BERBAHAN DASAR MINYAK JELANTAH SEBAGAI PENGGUNAAN LUMPUR PEMBORAN YANG RAMAH LINGKUNGAN - Rangga Wastu, Apriandi Rizkina; Yasmaniar, Ghanima; Husla, Ridha; Fattahanisa, Aqlyna (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2022)
The well drilling process is highly dependent on the performance of the drilling mud that is used. The use of oil-based mud that is more environmentally friendly continues to grow by utilizing environmentally friendly or biodegradable materials. This research was conducted to determine whether the use of used cooking oil or waste oil can be reused as a type of oil-based mud that has the same characteristics as Saraline mud or palm oil-based mud. The mud will be tested at several temperatures by testing the physical properties of the mud in the form of density and viscosity. The reference used in this study is the API 13B-2 standard laboratory specification. The result of this research is that the used cooking oil mud is successfully made if the oil water ratio (OWR) is changed to 90:10 and mix used cooking oil with saraline oil in a ratio of 50:50. Based on the tests that have been carried out on the physical properties of density, for samples of saraline mud and samples of used cooking oil mud at temperature of 100oF, there is no addition of barite because it is in accordance with the desired specifications, but for samples of saraline mud at temperatures of 200oF and 300oF, additives of barite are added of 25 gr and 40 gr, respectively, and for used cooking oil mud at temperatures of 200oF and 300oF, the addition of barite additives are 60 gr and 75 gr, respectively, so that all mud can meet the desired specifications. Meanwhile, in viscosity testing, the viscosity values of the samples of saraline mud and used cooking mud at temperatures of 100oF, 200oF, and 300oF, met the desired standard specifications.